The Impact of Self-Dependence and Mood on Students' Learning Commitment - Mohammad, Wily (Yayasan Sinergi Kawula Muda, 2023)
This quantitative research aims to investigate the influential role of self-dependence and mood-related factors on students' commitment within an educational context. Employing purposive sampling, 41 individuals from distinct classes in a Jakarta school were deliberately selected to ensure a diverse representation of the student population. Through meticulous collection of three primary variables, each comprising two indicators and analysis using SEM-PLS in SmartPLS 4, the study aims to offer a nuanced analysis of these aspects. The research findings reveal significant positive correlations between self-dependence attributes (with confidence and initiative as indicators) and mood (with good perception and good thoughts as indicators) on students' commitment levels. Fostering self-reliance, proactive learning behaviors, and a positive emotional environment emerges as crucial in enhancing students' commitment to their academic pursuits. The implications suggest the importance of targeted interventions and programs within educational institutions to fortify self-dependence and cultivate positive emotional climates, thus augmenting students' commitment and academic success.